Growth and Dielectric Properties of Monoclinic Gd2O3 on Si(001). (22nd October 2019) - Gribisch, Philipp; Roy Chaudhuri, Ayan; Fissel, Andreas
Abstract : Gadolinium oxide (Gd2 O3 ) was grown at low temperatures (250 °C) on Si(001) using molecular beam epitaxy. The crystal structure was investigated with X-ray diffraction experiments, where the crystal structure changes from cubic to monoclinic depending on the oxygen supply. We propose that Gibbs-Thomson effect is responsible for the change in crystal structure due to the initial nucleation of nanometer-sized islands and its variation in diameter depending on the growth conditions. The dielectric properties of the monoclinic structure were investigated using Capacitance-Voltage measurements, where platinum was used as contact material. Dielectric constants larger than 20 were obtained, which is higher than for the cubic structure. The monoclinic Gd2 O3 layers suffer from flat-band voltage instabilities, which is most likely due to defects located at the interface or near-interface region of the Gd2 O3 and silicon. Forming gas annealing results in an improvement of the dielectric behaviour.